Methodology for asking questions aimed at value creation in business - 六間口 壮吾; 湧井 正明; 古賀 美里; 伊藤 智一; 関口 通江; 岡 重文 (Bulletin of the Graduate School of Management, GLOBIS University, 2023)
We developed a Methodology for asking questions aimed at value creation in business and tested its validity. For the validation, we clarified the requirements for evaluating the questions, and then asked the businesspersons in the subject group to formulate questions by using case studies. As a result of the verification, we were able to confirm a certain level of validity of the methodology from two points of view: the questions received higher grades through the methodology, and the subjects felt that their thinking was facilitated by the methodology. On the other hand, it also became clear that, depending on the methodological process, there were cases in which the hypothesized practice did not affect the question scores, and we were able to confirm the direction of methodological refinement.